Long-Term Clinical Outcome of Arrhythmogenic Right Ventricular Cardiomyopathy in Individuals With a p.S358L Mutation in TMEM43 Following Implantable Cardioverter Defibrillator Therapy. (March 2016) - Hodgkinson, Kathleen A.; Howes, A.J.; Boland, Paul; Shen, Xiou Seegar; Stuckless, Susan; Young, Terry-Lynn; Curtis, Fiona; Collier, Ashley; Parfrey, Patrick S.; Connors, Sean P.
Abstract : Background—: We previously showed a survival benefit of the implantable cardioverter defibrillator (ICD) in males with arrhythmogenic right ventricular cardiomyopathy caused by a p.S358L mutation in TMEM43 . We present long-term data (median follow-up 8.5years) after ICD for primary (PP) and secondary prophylaxis in males and females, determine whether ICD discharges for ventricular tachycardia/ventricular fibrillation were equivalent to an aborted death, and assess relevant clinical predictors. Methods and Results—: We studied 24 multiplex families segregating an autosomal dominant p.S358L mutation in TMEM43 . We compared survival in 148 mutation carriers with an ICD to 148 controls matched for age, sex, disease status, and family. Of 80 male mutation carriers with ICDs (median age at implantation 31 years), 61 (76%) were for PP; of 68 females (median age at implantation 43 years), 66 (97%) were for PP. In males, irrespective of indication, survival was better in the ICD groups compared with control groups (relative risk 9.3 [95% confidence interval 3.3–26] for PP and 9.7 [95% confidence interval 3.2–29.6] for secondary prophylaxis). For PP females, the relative risk was 3.6 (95% confidence interval 1.3–9.5). ICD discharge-free survival for ventricular tachycardia/ventricular fibrillation ≥240 beats per minute was equivalent to the control survival rate. Ectopy (≥1000 premature ventricular complexes/24 hours) was the only independent clinical predictor of ICD discharge in males, and no predictor was identified in females. Conclusions—: ICD therapy is indicated for PP in postpubertal males and in females ≥30 years with the p.S358L TMEM43 mutation. ICD termination of rapid ventricular tachycardia/ventricular fibrillation can reasonably be considered an aborted death. Abstract : Supplemental Digital Content is available in the text.